Aqueous solution-processed, self-flattening AlOx:Y dielectrics for fully-transparent thin-film transistors. Issue 13 (September 2019) - Wu, Weihua; Liang, Lingyan; Yu, Jingjing; Xiao, Xi; Zhang, Hongliang; Gao, Junhua; Zhuge, Fei; Chang, Ting-Chang; Lan, Linfeng; Cao, Hongtao
Abstract: Dielectrics fabrication on rough substrates, always leading to microstructural defects and detrimental dielectric properties eventually, is a great challenge for academic endeavors in this field. We report here on self-flattening AlO x :Y dielectric thin films processed by a facile aqueous solution method. The obtained AlO x :Y dielectrics are dense, large-area uniform, and amenable to accurate control of film thickness by repeating the deposition cycles. In particular, an atomically smooth surface with a RMS of 0.10 nm was realized for the AlO x :Y film with a thickness of 14.5 nm on Si wafer, yielding a low leakage current density of 7.9 × 10 -8  A cm -2 @2 MV/cm, a dielectric constant of 8.8 @100 Hz, and an attenuated dielectric dispersion property. The interactions between pre-baked YO x underlayer and later-dropped AlO x precursor were comprehensively investigated, in order to understand the film growth mechanism and the origin of self-flattening effect. Fortunately, this self-flattening effect is also applicable to other substrates. A RMS of 0.81 nm was achieved on ITO glasses, and the height distribution profile of the film surface was found to follow symmetric Gaussian distribution. This preparation routine was also examined by device verification in the fully-transparent thin-film transistors. The combination of ease of preparation and attractive physical properties would provide a green-route solution platform for dielectric synthesis, for interface engineering, and for well-performed devices on rough substrates.